Measurement of D*±, D± and D±s meson production cross sections in pp collisions at √s = 7 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2016)
The production of D*±, D± and D±s charmed mesons has been measured with the ATLAS detector in pp collisions at √s = 7 TeV at the LHC, using data corresponding to an integrated luminosity of 280 nb-1. The charmed mesons have been reconstructed in the range of transverse momentum 3.5 < pT(D) < 100 GeV and pseudorapidity |η(D)|<2.1. The differential cross sections as a function of transverse momentum and pseudorapidity were measured for D*± and D± production. The next-to-leading-order QCD predictions are consistent with the data in the visible kinematic region within the large theoretical uncertainties. Using the visible D cross sections and an extrapolation to the full kinematic phase space, the strangeness-suppression factor in charm fragmentation, the fraction of charged non-strange D mesons produced in a vector state, and the total cross section of charm production at √s = 7 TeV were derived.